Dasar pemberian hakmilik tanah di Malaysia: analisis menurut perspektif Islam / Jasni Sulong, Mohd Marbawi Taha and Mohd Nasir Ayub - Sulong, Jasni; Taha, Mohd Marbawi; Ayub, Mohd Nasir (Universiti Teknologi MARA, Pulau Pinang, 2014)
In Malaysia, the land matter is vested to the State Government. The State Authority has almost unlimited power in disposing land either to individuals or organizations qualified under the law. Lately, the government tends to award land to individuals who raise the country's name such as sports players, government officials and politicians. This policy is often questioned by many parties especially in terms of the reasonableness of the grant and their capabilities to develop. Therefore, the objective of this paper is to examine whether the legal concept of land alienation in the country is in line with the teachings of Islam or otherwise. Generally, the research is based on library research. The analysis based on the traditional books of fiqh, the cases and the law statutes. Comparisons will be made between the practices of the Prophet Muhammad SAW and his Companions in the past with the present practice of law. The study concluded that the provisions in the land legislation are so open that it may lead to the abuse of power in the administration. Therefore, this article proposes that the system of land alienation be controlled by setting strict requirements and rigid principles based on "maslahah " and "siyasah syar'iyyah".